La Finestra come genesi della poesia: la dialettica del fuori e del dentro in Tabacaria. Nuovi percorsi estetici nella poesia pessoana (Altre Modernità, 2015)
The window can include a lot of different symbolic values and can be considered at the same time a border and a protection area: this architectural element allows the pessoan heteronomy Álvaro de Campos to observe other people’s life, taking place in the road. His gaze, attentive and absorbed at the same time, leads to the birth of the poem Tabacaria (1928). It is a poem that from the beginning portrays the collapse of illusion: the poet is a man who chooses not to live his own life, preferring to take refuge behind a window, a profound disillusionment narrated through the dialectics of ‘outside and inside’. In Tabacaria the window allows two opposing worlds – otherwise incompatible – to come together, although they remain separate, a contrast defined by the Pessoa-Campos as alienating, reminiscent of the perceptual dialectic theorized by the philosopher Merleau-Ponty. A window, an architectural barrier that allows you to see and be seen at the same time, putting together two seemingly irreconcilable worlds. ‘Tecnema’, which has always fascinated and here becomes the place of observation of the ‘tabacaria’, is the symbol of an illusory world. From a real and ordinary situation, ‘finished’ and enclosed by the walls of the attic, the poet conveys a feeling of infinity, eternity, through an expansion of the senses disintegrated from the tediousness of the existential poetic subject.